Polymorphism of 16s rRNA Gene: Any Effect on the Biomolecular Quantitation of the Honey Bee (Apis mellifera L., 1758) Pathogen Nosema ceranae? - Giovanni Cilia; Giacomo Luchetti; Antonio Nanetti (Applied Sciences, 2022)
The microsporidian Nosema ceranae is a severe threat to the western honey bee Apis mellifera, as it is responsible for nosemosis type C, which leads the colonies to dwindle and collapse. Infection quantification is essential to clinical and research aims. Assessment is made often with molecular assays based on rRNA genes, which are present in the N. ceranae genome as multiple and polymorphic copies. This study aims to compare two different methods of Real-Time PCR (qPCR), respectively relying on the 16S rRNA and Hsp70 genes, the first of which is described as a multiple and polymorphic gene. Young worker bees, hatched in the laboratory and artificially inoculated with N. ceranae spores, were incubated at 33 °C and subject to different treatment regimens. Samples were taken post-infection and analyzed with both qPCR methods. Compared to Hsp70, the 16S rRNA method systematically detected higher abundance. Straightforward conversion between the two methods is made impossible by erratic 16s rRNA/Hsp70 ratios. The 16s rRNA polymorphism showed an increase around the inoculated dose, where a higher prevalence of ungerminated spores was expected due to the treatment effects. The possible genetic background of that irregular distribution is discussed in detail. The polymorphic nature of 16S rRNA showed to be a limit in the infection quantification. More reliably, the N. ceranae abundance can be assessed in honey bee samples with methods based on the single-copy gene Hsp70.